CYTOTOXIC ACTIVITY OF Anredera cordifolia LEAF EXTRACT ON HELA CELLS - Dita Maria Virginia; Roni Permana Saputra; Agustina Setiawati (BIOTROPIA, 2019)
Cervical cancer is the second most frequently occurring cancer among females worldwide. Since the best strategy against cancer is to kill cancer cells without endangering normal cells, discovering a potentially selective anticancer agent from plants has become a major focus for researchers globally. A previous study on Anredera cordifolia, known as binahong in Indonesia, revealed its cytotoxic activity on HeLa cervical cancer cells with an IC₅₀ value of 75 µg/mL. However, the selectivity of the chemical agent and its molecular target was not investigated. Therefore, this study aimed to determine the selectivity of ethanolic extract of Anredera cordifolia leaf (EAC) on Vero cells and its molecular target on HeLa cells. The extract was prepared by macerating A. cordifolia leaf powder in 70% ethanol. The viability of Vero cells was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, while the cell cycle of HeLa cells was analyzed using flow cytometry. The molecular target of the extract was further investigated using immunocytochemical staining. The results demonstrated the selective cytotoxicity of EAC against HeLa cells compared to Vero cells, with a Selectivity Index (SI) of 17.36. The extract induced cell cycle arrest at the G1/S phase and suppressed Bcl-2 expression, an anti-apoptotic protein that also regulates cell cycle progression. These findings support the potential use of A. cordifolia leaf extract as a promising anticancer agent against cervical cancer, particularly HeLa cells.